Pendampingan Upaya Pencegahan Virus Covid-19 Sejak Dini Melalui Sosialisasi Dan Edukasi Terhadap Santri TPQ Al Fattah Kademangaran - Ali Mu’tafi (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2022)
Covid-19 is a dangerous respiratory disease caused by the corona virus. At first, this outbreak was in Wuhan, China, then quickly spread throughout the world and caused a global pandemic. An understanding of Covid-19 is needed. This article is the result of community service activities carried out in Rt 03/ 02, Desa Kademangaran Village, which aims to provide understanding to TPQ Al Fattah students about the Covid-19 virus and how to prevent its infection through socialization and education. This activity is one of the efforts to stop the transmission of the Covid-19 virus, it is hoped that with this activity TPQ Al Fattah students can understand the challenges of Covid-19 and how to prevent it so they can participate in efforts to prevent the transmission of the Covid-19 virus starting from themselves. each of them, given the importance of socialization and education movements about Covid-19 as it is today, because very few people, especially children, have an understanding of the virus that is spreading throughout the world.